The Innovative and modern methods teaching English language - Jonuzoqova, Zebiniso (Журнал иностранных языков и лингвистики, 2021)
ABSTRACT: this article describes the innovative and interesting methods teaching English language. This article characterizes combining two types which are traditional and modern methods of teaching and how we can make our teaching very effective and useful. Keywords: atmosphere, evaluated, modern, Innovative.